Review of Janet E. Smith, Self-Gift: Essays on Humanae Vitae and the Thought of John Paul II - John Sikorski (Journal of Moral Theology, 2021)
Review of Janet E. Smith, _Self-Gift: Essays on_ Humanae Vitae _and the Thought of John Paul II_